Beijing film academy 2019. (Intellect China library, 2022)
The Beijing Film Academy Yearbook highlights the best academic debates, discussions and research, as published in the highly prestigious Journal of Beijing Film Academy in 2019. This volume brings together specially selected articles, appearing in English for the first time, to bridge the gap in cross-cultural research in cinema and media studies.